Assessing the Impact of Goods Receiving and Storage Issues on Warehouse Operational Effectiveness: Evidence from Belviu Hotel Bandung - Yuni Lisdianingsih; Kartika Dewi (ASEAN Journal on Hospitality and Tourism, 2026)
Warehouse management is a crucial part of supporting smooth hotel operations. This study was conducted to analyze problems that occur in the process of receiving and storing goods at the Belviu Hotel Bandung warehouse and their impact on warehouse operational effectiveness. The research method used was descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research findings identified several major challenges, including discrepancies in the quantity and condition of goods upon receipt, inadequate warehouse infrastructure, and an inefficient stock management system, which led to damaged goods. These issues disrupted the availability of goods and affected operational costs and coordination between departments. The recommended solutions include improving staff capabilities through goods receiving training, strengthening coordination with suppliers and related departments, optimizing the implementation of the FIFO system, and providing adequate warehouse facilities. Maximizing the use of technology for goods recording, implementing audits, and conducting routine double-checks are highly recommended to minimize errors.